(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background/Aims: The treatment of schizophrenia is commonly viewed from a pharmacological and social perspective, but issues of nutrient intake are seldom examined. However, the various study reported that polyunsaturated fatty acids (PUFAs) concentration is reduced in the plasma of schizophrenic. Therefore PUFAs intake may have a correlation with symptom severity of schizophrenic. This study aimed to assess the PUFAs intake of schizophrenic and its correlation with symptom severity of of schizophrenic. Method: This cross-sectional study was conducted on 63 schizophrenia hospitalized patients in Ernaldi Bahar Hospital, South Sumatra, Indonesia. The symptom severity of of schizophrenic were determined using the validated Indonesian version of PANSS. Dietary intake was assessed using a 3-day food weighing. Correlation between variables was determined using the Spearman Correlation Coefficient. Results: The result showed a significant negative correlation between omega-3 fatty acids and Positive scale, Negative Scale, General psychopathology and risk of aggression with r=-0.345, r= -0.408, r= -0.483, and r= -0.406 respectively (p<0.01). The omega-6 fatty acids intake were negatively correlated with Positive scale, Negative Scale, General psychopathology and risk of aggression with r= -0.390, r= -0.496, r=-0.525, and r=-0.389 respectively (p<0.01). A statistically significant correlation was seen between ratio of omega-6/ omega-3 and Positive scale, Negative Scale, General psychopathology and risk of aggression with r=0.249, r= 0.256, r= 0.356, r=0.343 respectively (p<0.01). Conclusion: These findings suggest that increasing PUFAs intake might have a positive health outcome in of schizophrenic.